USEFUL LIFE OF INTANGIBLE ASSETS IN BUDGET ORGANIZATIONS (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
In this scientific research work, the issues of determining the useful life of intangible assets in budget organizations are highlighted. Determining the useful life of intangible assets in budget organizations and the factors affecting it have been scientifically and practically studied.